2006
DOI: 10.1063/1.2360253
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric long period fiber gratings fabricated by use of CO2 laser to carve periodic grooves on the optical fiber

Abstract: An asymmetric long period fiber grating ͑LPFG͒ with a large attenuation of −47.39 dB and a low insertion loss of 0.34 dB is fabricated by use of focused CO 2 laser beam to carve periodic grooves on one side of the optical fiber. Such periodic grooves and the stretch-induced periodic microbends can effectively enhance the refractive index modulation and increase the average strain sensitivity of the resonant wavelength of the LPFG to −102.89 nm/ m . The resonant wavelength and the peak attenuation of the LPFG c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
98
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(98 citation statements)
references
References 11 publications
0
98
0
Order By: Relevance
“…Compared with the UV-laser exposure technique, the CO 2 laser irradiation technique is much more flexible and low cost because no photosensitivity and any other pretreated process are re-quired to write a grating in the glass fibers. [16][17][18][19][20][21][22][23][24][25][26][27][28][29] Moreover, the CO 2 laser irradiation process can be controlled to generate complicated grating profiles via the well-known point-topoint technique without any expensive masks. This technique could be, hence, used to write LPFGs in almost all types of fibers including pure-silica photonic crystal fibers ͑PCFs͒.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with the UV-laser exposure technique, the CO 2 laser irradiation technique is much more flexible and low cost because no photosensitivity and any other pretreated process are re-quired to write a grating in the glass fibers. [16][17][18][19][20][21][22][23][24][25][26][27][28][29] Moreover, the CO 2 laser irradiation process can be controlled to generate complicated grating profiles via the well-known point-topoint technique without any expensive masks. This technique could be, hence, used to write LPFGs in almost all types of fibers including pure-silica photonic crystal fibers ͑PCFs͒.…”
Section: Introductionmentioning
confidence: 99%
“…5-15 Since Hill et al 1 and Vengsarkar et al 5 wrote the first FBG and LPFG in conventional glass fibers in 1978 and 1996, respectively, the fabrications and applications of in-fiber gratings have achieved rapid developments. Various fabrication methods, such as ultraviolet ͑UV͒ laser exposure, 5-15 CO 2 laser irradiation, [16][17][18][19][20][21][22][23][24][25][26][27][28][29] electricarc discharge, [30][31][32][33][34][35][36][37] femtosecond laser exposure, [38][39][40][41][42][43] mechanical microbends, [44][45][46][47][48][49][50][51] etched corrugations, [52][53][54][55][56][57] and ion beam implantation, [58][59][60] have been demonstrated to write LPFGs in different types of optical fibers. Numerous LPFGbased devices have ...…”
Section: Introductionmentioning
confidence: 99%
“…2,4 Besides the approach with evanescent waves from nanometer fiber tips coated with gold particles, 5 a majority of fiber sensors for refractive index measurement utilized fiber gratings, i.e., long-period gratings ͑LPGs͒ and fiber Bragg gratings ͑FBGs͒. Recent work that reported refractive index measurement with LPGs are either gold coated, 6 arc-induced phase shifted, 7 asymmetric, 8 or inscribed in air-and water-filled photonic crystal fibers. 9 Reported refractive index measurement with FBGs includes a metal-coated grating in a special single-mode fiber of larger core ͑26 m͒ and thinner cladding ͑30 m͒, 10 a tilted FBG with gold coating in single-mode fiber, 11 and cladding mode resonances of etched-eroded FBG.…”
mentioning
confidence: 99%
“…An asymmetrical LPFG with 20 periods and a grating pitch of 400 m were written in a standard singe mode fiber (SMF) by the use of the CO 2 -laser-carving technique reported in [13]. Periodic grooves were carved on the single-side surface of the fiber, as shown in Fig.…”
Section: Applying Tensile Strainmentioning
confidence: 99%
“…In other words, they are so-called preprocessing techniques [12]. Authors recently reported a novel technique for writing an asymmetric LPFG by means of carving periodic grooves on the surface of an optical fiber with a focused CO 2 laser beam [13]. Mode coupling in such an asymmetrical CO 2 -laser-induced LPFG with periodic grooves is very sensitive to the tensile strain applied and the change in external temperature.…”
Section: Introductionmentioning
confidence: 99%